The Role of Genicular Nerve Blocks in Enhancing Postoperative Pain Management After Total Knee Arthroplasty: A Retrospective Study - Yuki Aoyama; Shinichi Sakura; Yoshimi Nakaji; Kornkanok Yuwapattanawong; Tetsuro Nikai (Anesthesiology Research and Practice)
Conclusion: The results of this exploratory retrospective study suggest that the additional benefits of GNBs, if any, are limited for the early postoperative period when combined with continuous FTB and iPACK block in patients undergoing TKA. However, larger, sufficiently powered, and more robust clinical trials are needed to confirm the present results.